Arranjos produtivos locais (APLs) no estado do Espírito Santo: política pública, processo decisório e percepção de atores - Vieira, Larissa Haddad Souza (2016)
The study of productive agglomerations points the State as the protagonist in supporting inter-institutional cooperation in terms of increased competitiveness of companies in various sectors, promoting regional development through public policies. This research analyzed the design of Local Productive Arrangements (LPAs) in the state of Espírito Santo (ES) as instruments of public policy for local development, according to the perception of strategic actors about decision-making processes present throughout the implementation of the National Policy support to LPAs, from the analysis of LPAs of Agro Tourism, Metal-Mechanic and Ornamental Stones. The case of Cluster Quesero de Villa María complements the analysis, highlighting similarities and differences between productive agglomerations supported by public policies in Brazil and Argentina. The study used as a theoretical basis Decision-making Process and Veto groups acting in public policies, the incremental approach and multilevel governance, and the reference on LPAs. The research, qualitative, used interviews to capture the perceptions of relevant actors to the implementation of policies in ES and Villa María about the decision-making process, its members and relations. Bibliographic and documentary data sources were also used, and the information went through Content Analysis. The results indicate incremental characteristics throughout the operative chain formed by several different decision processes. There were identified a few effects of the National Policy in its implementation in ES, and a decline in the use of LPAs approach in the state. All productive agglomerations were organized by top-down initiatives; however, two of them developed bottom-up characteristics due to the appropriation of its members on the proposals in development. Productive agglomerations were analyzed as features such as: Performance of Governance; Heterogeneity of Decision Maker Group; LPA Organization flow; Relationship with Government; Existence of Workers Groups Participation Channels and Local Community. The study identifies the asymmetrical relations between the actors in decision-making processes, both in the Brazilian and the in Argentinean cases, derived asymmetries as to information, access to participation and decision-making by groups related to its development. Business, government and supporting institutions groups are protagonists in these decision-making processes, while social and labor representations, even though relevant to LPAs, do not participate in them. The inclusion of different actors with diverse interests in decision-making processes, on the one hand, can generate conflicts and decision-making slow, but, in contrast, tends to generate decisions, changes and more integrated actions to local realities, according to different points of view and, therefore, more effective and intelligent. Moreover, the purpose of local development, by encouraging the LPAs, can be achieved to the extent that these actors are included in decision-making, because only so, it would be possible to achieve development in its perspective association between economic dynamism and improve the population's quality of life with a view to sustainability.